Fostering Literacy and Learning Innovation: The Interactive Flipbooks in an Educational E-Library - Elsita Lisnawati Guntar; Ida Ayu Oka Purnami; I Made Agus Oka Gunawan (Universitas Pendidikan Ganesha, 2025)
Low students’ reading interest and the predominant use of conventional teaching methods remain significant challenges in contemporary education. To address these issues, a community service program was conducted for teachers in schools that primarily rely on traditional instructional approaches and require training in interactive learning media. This program aimed to enhance teachers’ competencies in developing and utilizing interactive instructional media, particularly flipbooks, to improve students’ literacy and learning motivation. The implementation method was structured into three stages: problem identification, needs analysis, and program implementation. A total of 43 teachers from various subject areas participated in the training, which covered digital literacy concepts, the use of simple electronic learning media, and hands-on practice in creating and applying flipbooks in classroom settings. The results indicated that the training was highly effective in improving participants’ understanding and practical skills. Most participants reported that the program was very helpful (83.4%) and provided significant benefits (89.2%). The teachers successfully developed interactive flipbooks that, when implemented in classroom instruction, were shown to significantly enhance students’ learning motivation and comprehension. Overall, this activity empowered teachers with new pedagogical skills and inspired the adoption of more innovative teaching practices, highlighting the strong potential of flipbooks and e-libraries in advancing education in the digital era.